Έλεγχος ανοικτού βρόχου βηματικού κινητήρα μέσω του μικροελεγκτή Arduino - Φιορέτος, Σπύρος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Ηλεκτρικών Βιομηχανικών Διατάξεων και Συστημάτων Αποφάσεων, 2015)
This essay is about controlling a hybrid two phase step motor via an open loop control system based on Arduino Uno microcontroller. We program the microcontroller so that the system can perform all the basic functions that a step motor is capable of. All the excitation modes are possible. We constract the motor’s speed profile through a numerical method so that we can monitor it’s behaviour in a step by step manner. Knowing the speed profile we can deside if a particular step motor is suitable for a specific application or not. We can examine if the motor can fullfill all the requirements imposed by the system designer. For example if the motor is capable of reaching it’s pull out rate, or to perform a specific number of steps in a certain amount of time. A more intresting requirement is if we want the motor to excecute a specific number of steps with a specific speed within a very strict time frame without missing the target possition. We can confront such requirements in robotics, CNC machines, plotters and other modern machinery. Arduino Uno in coinjunction with the Adafruit motor shield has been proven a very reliable software – intensive solution for many small to mid – scale projects. AF_Motor.h and AcceStepper.h libraries provide many functions that can be very usefull when it comes to programming the system.